Minat Pengembangan Kompetensi Pelaut Indonesia - Arif Rahman; Mahardhika Andiansyah; Sarinten Sarinten; Ardiansyah Ardiansyah; Budi Ismanto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
This research aims at analyzing the effect of person job fit, working environment and job satisfaction simultaneously toward seafarers’ willingness in improving competencies. Quantitative approach is used in this research with purposive sampling in data collection. It has 380 BP3IP Jakarta’s graduates year 2016 to 2019 as the sample. Data analysis used is structural equation model (SEM) with Statistical Package for Social Science (SPSS) program, 22nd version and PLS for Structural Equation Modelling (SEM). The result shows that there is a significant effect of person job fit, working environment, and job satisfaction simultaneously toward seafarers’ willingness in improving competencies.